P308 Timing of initiation of HIV treatment and level of adherence among pregnant women under option b+ programme in nigeria. (14th July 2019) - Omonaiye, Olumuyiwa; Nicholson, Pat; Kusljic, Snezana; Manias, Elizabeth
Abstract : Background: Nigeria has the highest rate of mother-to-child transmission (MTCT) of HIV in the world. Adherence to antiretroviral therapy (ART) is therefore crucial in pregnancy because missed doses may lead to virological failure and increased risk of MTCT. Research has shown that ART commenced before pregnancy and continued throughout the prenatal period is associated with low rates of MTCT. We evaluated ART dose adherence among pregnant women who commenced ART before and after conception under the Option B+ programme in Nigeria. Methods: A standardized survey was used to obtain information about health behaviours and practices associated with ART use among pregnant women in four high-volume HIV treatment centres in Nigeria. A woman was considered adherent if she had not missed her ART dose over a four-day period. Prevalence of self-reported 100% adherence to ART doses was calculated for the previous four days using the bootstrap technique. Results: The survey had a response rate of 92.6%. Of the 275 women, 34.2% had commenced ART before conception, while 24.7%, 36.4% and 4.7% started ART during the first, second and third trimester of the current pregnancy respectively. Of women starting ART before conception, 51.1% (95% CI: 41.5 to 60.6) were adherent. Of the women who commenced ART after conception, 30.9% (95% CI 20.6 to 42.6), 19.0% (95% CI 12.0 to 28.0) and 15.4% (95% CI 0 to 38.5) were adherent in the first, second and third trimester respectively. Conclusion: Adherence was highest among women who started ART before conception and lowest among women who commenced ART during the third trimester. Overall, adherence levels were low. It is essential that ART adherence is improved during pregnancy to fast track the elimination of MTCT in Nigeria. It may be helpful to commence screening for HIV status before pregnancy to facilitate early commencement of ART, if required. Disclosure: No significant relationships.